Combinatorial Antitumor Effect of Rapamycin and β-Elemene in Follicular Thyroid Cancer Cells. (4th May 2016) - Zhou, Jun; He, Li-Li; Ding, Xiao-Fei; Yuan, Qiu-Qi; Zhang, Jian-Xin; Liu, Shuang-Chun; Chen, Guang
Abstract : Background. mTOR signaling would be a promising target for thyroid cancer therapy. However, in clinical trials, objective response rate with mTOR inhibitor monotherapy in most cancer types was modest. A new focus on development of combinatorial strategies with rapalogs is increasing. Objective. Investigating the combinatorial antitumor effect of rapamycin and β -elemene in follicular thyroid cancer cells. Methods. MTT assay was used to determine the FTC-133 cell proliferation after culturing with rapamycin and/or β -elemene. To analyze their combinatorial effect, immunoblotting was performed to analyze the activation status of AKT. Moreover, β -elemene attenuated rapamycin-induced immunosuppression was tested in mice. Results. Combination of rapamycin and β -elemene exerted significant synergistic antiproliferative effects in FTC-133 cell lines in vitro, based on inhibiting the AKT feedback activation induced by rapamycin. In vivo, the β -elemene could attenuate rapamycin-induced immunosuppression via reversing imbalance of Treg/Th17, with the underlying mechanism needed to be declared. Conclusions . We demonstrate that the novel combination of mTOR inhibitor with β -elemene synergistically attenuates tumor cell growth in follicular thyroid cancer, which requires additional preclinical validation.